Development of a modern prejudice toward juveniles scale (MPJS) and its psychometric properties - Mukai, Tomoya (Psychology, crime & law, 2025)
The treatment of juvenile offenders remains a problem of broad interest in many societies. The current study aimed to develop and validate a Modern Prejudice toward Juveniles Scale (MPJS) and examine its psychometric properties, including its relationships with preferences in juvenile criminal policy. Study 1 (N = 266) investigated the factor structure of item candidates when respondents were instructed to think of 18- and 19-year-olds as juveniles. An exploratory factor analysis yielded a two-factor model, with each having acceptable reliability. Additionally, based on the characteristics of each item, which were examined using the graded response model, 10 items were retained in the provisional scale. The multi-group confirmatory factor analysis conducted in Study 2 (N = 866) confirmed the two-factor model and its generalizability to other age groups (i.e. 16/17 and 14/15). Convergent validity with social dominance orientation and right-wing authoritarianism, incremental validity with support for harsher punishment and rehabilitation, and real-name reporting were examined and confirmed. Overall, the results support the reliability, convergent validity, and incremental validity of the MPJS.